2011
DOI: 10.14742/ajet.975
|View full text |Cite
|
Sign up to set email alerts
|

Framing ICT implementation in a context of educational change: A structural equation modelling analysis

Abstract: Despite the common belief that information and communication technology (ICT) has the potential to support certain fundamental changes in learning, few have examined ICT implementation conceptually within a wider context of educational change. Methodologically, we are by and large limited to building simple models that accommodate only a single dependence relationship among variables. Framing ICT implementation as a process of interactions among pedagogical and organisational factors in bringing about changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 33 publications
1
15
0
4
Order By: Relevance
“…Through the establishment of teaching portfolios, teachers can provide records of professional development and proof of their accomplishments. In this way, teacher professional development is guaranteed, student learning accomplishments are assured, and instruction can be affirmed by the public at large (Wong & Li, 2011).…”
Section: Influence Of Teachers Using E-portfolios To Improve the Evalmentioning
confidence: 99%
See 2 more Smart Citations
“…Through the establishment of teaching portfolios, teachers can provide records of professional development and proof of their accomplishments. In this way, teacher professional development is guaranteed, student learning accomplishments are assured, and instruction can be affirmed by the public at large (Wong & Li, 2011).…”
Section: Influence Of Teachers Using E-portfolios To Improve the Evalmentioning
confidence: 99%
“…In other words, if the technological functions to be used by the teacher can make the task smoother, the user's costs in carrying out the task will be lowered. Only when it can support the task to be completed will there be good work performance (Wong & Li, 2011).…”
Section: Teacher Evaluation Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, leadership has throughout history been researched in terms of leaders' traits such as intelligence or self-confidence; emotional intelligence; leaders' styles; or the nature of interactions between leaders and subordinates, and is described in terms of the ability of leaders to inspire and motivate a group to accomplish common goals (Northouse, 2013). In addition, recent research of leadership have demonstrated its impact on student achievement (Hallinger & Heck, 2010;Leithwood & Jantzi, 2012) and on technology integration (Anderson & Dexter, 2005;Wong & Li, 2011;Baylor & Ritchie, 2002) in terms of seeing it as a collective property, distributed throughout a school community . This research has framed effective leadership as not always looking the same in each context, but rather maintaining certain core practices that apply not only to leadership for student achievement, but also to leadership for the effective integration of personalized learning with one-to-one technology.…”
Section: Technology Leadershipmentioning
confidence: 99%
“…Furthermore, theories such as transformational leadership (Kouzes & Posner, 1987;Leithwood & Janzi 2006;Wong & Li, 2011) detail the importance of a strong, widelyshared vision that motivates individuals to exert efforts towards that vision. Integrating one-one devices in the absence of a widely shared vision and goals may have resulted in teachers integrating technology to meet their instructional demands and maintain traditional teacher-centered instructional methods (Cuban, 2013;Lowther et al, 2012;Shapley, 2010).…”
Section: Finding 1: Leaders Articulated Limited Definitions Of Personmentioning
confidence: 99%